Present a new method for increasing the intelligence and speed of the Firefly algorithm - Fariba Solaymani; Narges Salehpour; Mohammad Nazari Farokhi (مدیریت مهندسی و رایانش نرم)
Today, Most important issues in the industry of non-linear and multi-parametric are considered optimization problems. On the other hand, the attractiveness of the behavior and interaction of animals has led the computer scientists, inspired by these interactions to create algorithms for optimization problems, which in many cases provide quick and acceptable solutions to complex problems. One of the propagation intelligence algorithms is firefly algorithm, which is bace on the exposure of luminous worms and their absorption into more light. The main problem with algorithms Such as firefly is that takes a lot of time to convege the desired answers. So if the number of firefly worms is more than 128, their run time with CPU is 2.5820 milliseconds but with using GPU 1.5090 milliseconds. In this paper, we intend to use a pc graphics unit to provide a version of the firefly algorithm that converages to the desired solutions more quickly while maintaining accuracy.